Gender identity and research relationships - Ward, Michael Rhys Morgan; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
Many researchers in recent years have begun to reflect on their gender identity and how this impacts on the research process and discuss how this helps build rapport with participants and creates successful or unsuccessful pieces of qualitative research. However, how does this intersect with other forms of identity, such as class, ethnicity, disability, age, sexuality? In this volume contributors explore these issues by reflecting on their own studies and research careers and address how important or unimportant gender has been in building research relationships. While the gender identity of the respondent/researcher relationship is undoubtedly important, what must also be acknowledged are the attributes which create a good fieldworker and competent social science researchers capable of understanding and engaging in different social situations and thought interaction with different participants.
Time to kill the witch? reflections on power relationships when leaving the field / Sara Delamont -- Masculinity, age and rapport in qualitative research / Thomas Thurnell-Read -- Betweenness and the negotiation of similarity and difference in the interview setting: reflections on interviewing grandfathers as a young, female researcher / Anna Tarrant -- A monster lurking in the shadows? one researchers crisis of representing class and gender / Alexandra Allan -- Similarity and familiarity: reflections on indigenous ethnography with mothers, daughters and school teachers on the margins of contemporary wales / Dawn Mannay, Jordon Creaghan -- Staying onside on the inside: men, masculinities and the research process / Andrew Parker -- 'Let me know when you figure everyone around here out': placing gender in the ethnographic process / Edward W. Morris -- Relationship-building in research: gendered identity construction in researcher-participant interaction / Garth Stahl -- Is she one of us? intersecting identities and social research / Nathalie Lozano-Neira, Jen Marchbank -- Research with queers, peers and elites: a queer/feminist approach to participant demographics / Leslie Sherlock.
Includes bibliographical references.
Keywords: Social Science -- Gender Studies; Gender studies, gender groups; Sociology -- Methodology; Gender identity; Qualitative research; Electronic books